Komunikasi Keluarga Asia dalam Film “Turning Red” Analisis Semiotika Roland Barthes - Eksa Tri Imarti; Silviana Purwanti; Rina Juwita (Jurnal Sosial Teknologi, 2026)
Family communication is an important aspect in shaping individual character, values, and identity, especially in Asian families that are known to have a communication pattern based on obedience and collectivism values. The film Turning Red represents the dynamics of Asian family communication through the conflict between the demands of family traditions and the needs of adolescent self-expression. This study aims to analyze the meaning of Asian family communication shown in the film through Roland Barthes' semiotic approach, including the meaning of denotations, connotations, and myths, and examine family communication patterns based on the concept of Family Communication Patterns, namely conformity orientation and conversation orientation. This study uses a qualitative method with semiotic analysis techniques on selected scenes that depict the family interaction of the main character. The results of the study show that Asian family communication in this film represents the dominance of the values of parental obedience, family control over children, and the process of negotiating adolescent identity in the family. In addition, it was found that open communication can be a solution in alleviating family conflicts. The conclusion of this study shows that the film Turning Red is not only an entertainment medium, but also represents the reality of Asian family communication which is full of cultural values, social pressures, and the importance of a balance between obedience and open communication within the family